From slaves to servant leaders: remembering the contributions of John Merrick and Alonzo Herndon - Prieto, Leon; Phipps, Simone; Mathur-Helm, Babita (Society and Business Review, 2018)
Purpose The purpose of this paper is to contribute to knowledge in the field of business by recognizing two historic entrepreneurs who played an important role in the African-American community, and by viewing their contributions through the lens of servant leadership. Design/methodology/approach The study is conducted by reviewing and synthesizing a number of writings from sources, such as history journals, newspapers and other resources. Findings The main finding is that two former slaves (Merrick and Herndon) practiced servant leadership in the early twentieth century as a way to create jobs and transform communities. Originality/value The contributions made by African-Americans have not been adequately covered in the literature. This paper begins to fill a noticeable void by highlighting the contributions of two former slaves who managed to become successful servant leaders within their communities.
Keywords: Business History and race